Exotic plant responses to large-scale commercial logging in ponderosa pine forests of the Black Hills National Forest, South Dakota, USA - Jack L. Butler; Stefanie D. Wacker; Jacqueline P. Ott; Scott Baggett; Michael A. Battaglia (Forest Ecology and Management, 2025)

Refining spiny lobster (Panulirus argus) escape and mortality estimates in Florida’s lobster trap fishery using long-term video - Casey B. Butler; Jack Butler; William C. Sharp; Thomas R. Matthews (Fisheries Research, 2024)

Management practices, and not surrounding habitats, drive bird and arthropod biodiversity within vineyards - Natalia B. Zielonka; Jack D. Shutt; Simon J. Butler; Lynn V. Dicks (Agriculture, Ecosystems & Environment, 2024)

Emerging, Low-Cost Ocean Observing Technologies to Democratize Access to the Ocean - Jack Butler; Camille Pagniello (Oceanography, 2021)

An Optical Imaging System for Capturing Images in Low-Light Aquatic Habitats Using Only Ambient Light - Camille Pagniello; Jack Butler; Annie Rosen; Addison Sherwood; Paul Roberts; Edward Parnell; Jules Jaffe; Ana Širović (Oceanography, 2021)
It is preferable that methods for monitoring fish behavior, diversity, and abundance be noninvasive to avoid potential bias. Optical imaging facilitates the noninvasive monitoring of underwater environments and is best conducted without the use of artificial lighting. Here, we describe a custom-designed optical imaging system that utilizes a consumer-grade camera to capture images in situ in ambient light. This diver-deployed system can be used to collect time series of occurrences of animals while concurrently obtaining behavioral observations for two weeks to a month (depending on the sampling rate). It has also been configured to be paired with a passive acoustic system to record time-synchronized image and acoustic data. The system was deployed in a protected kelp forest off southern California and captured >1,500 high-quality images per day over 14 days. The images revealed numerous fish species exhibiting biologically important behaviors as well as daily patterns of presence/absence. The optical imaging system is a cost-effective tool that can be easily fabricated and improves upon many of the limitations of previous systems, including deployment length and image quality in low-light and limited-visibility conditions. The system provides a relatively noninvasive way to monitor shallow marine habitats, including protected areas, and can augment traditional survey methods by providing nearly continuous observations and thus yield increased statistical power.

Response of Fish and Invertebrate Larvae to Backreef Sounds at Varying Distances: Implications for Habitat Restoration - Emily R. Anderson; Jack Butler; Mark J. Butler (Frontiers in Marine Science, 2021)
Underwater sound is used by many marine larvae to orient to coastal habitats including backreef, sponge-dominated hardbottom habitat in the Florida Keys (FL, United States)—a particularly “noisy” coastal habitat. However, the distance over which acoustic cues are attractive to settlement-stage larvae is generally unknown. We examined this phenomenon in a region of the Florida Keys where mass sponge die-offs have diminished both underwater soundscapes and larval settlement. The absence of pronounced hardbottom-associated sound over such a large area allowed us to experimentally test in situ the response of fish and invertebrate larvae to broadcasted sounds at different distances from their source. We first measured the signal-to-noise ratio of healthy hardbottom habitat soundscapes broadcast from an underwater speaker at seven distances to determine the maximum range of the signal. Based on those results, larval collectors were then deployed at 10, 100, 500, and 1,000 m from speakers broadcasting sounds recorded at either degraded or healthy hardbottom sites for five consecutive nights during each of three new and full moon periods in summer/fall 2019. Larval settlement onto those collectors was affected by lunar phase and soundscape type, but varied among species. In most cases, the effect was small and not likely to be ecologically significant. The absence of a strong larval settlement response to a sound cue lies in contrast to results from other studies. We suspect that the small (<500 m) radius of the broadcasted soundscapes may have limited the magnitude of the larval response to locally available larvae whose abundance may have been low because the experiment was conducted within a large, relatively quiet seascape. If true, it is possible that planktonic larvae may require a series of acoustic “sign-posts,” perhaps in combination with other cues (e.g., chemical), to successfully orient to distant nursery habitats. Although habitat restoration efforts may be able to restore healthy soundscapes, the typically small size and number of restoration sites may limit the range of the acoustic cue and thus larval attraction to restored habitats.

Diel and Seasonal Variability in Kelp Forest Soundscapes Off the Southern California Coast - Jack Butler; Camille M. L. S. Pagniello; Jules S. Jaffe; P. Ed Parnell; Ana Širović (Frontiers in Marine Science, 2021)
Soundscape ecology is a relatively new field that can provide insights into the structure and health of marine habitats. Though this field is growing, the acoustics of many marine habitats, including the giant kelp forests off Southern California, remain poorly studied. Here, we examine the diel and seasonal periodicity of kelp forest soundscapes within a protected and unprotected site off San Diego, CA. Singular value decomposition was used to identify frequency bands of interest, enabling tracking of these bands through seasons to examine their variability. Four frequency bands were identified: (1) 60–130 Hz, which encompassed a putative fish chorus, (2) 300–500 Hz, which encompassed a different putative fish chorus, (3) a band that encompassed humming generated by Plainfin Midshipmen Poricthys notatus (fundamental frequency: 85–95 Hz, and two subharmonics 175–185 Hz and 265–275 Hz), and (4) a band that encompassed the snaps of snapping shrimps from 2.5 to 7.5 kHz. Overall, kelp forest soundscapes exhibited diel and seasonal variability. In particular, the two putative fish choruses dominated the dusk soundscapes during late spring and summer, and the Midshipmen hums persisted throughout nights in summer. Snapping shrimp sounds exhibited stereotypic crepuscular activity, with peaks in acoustic energy in the 2.5–7.5 kHz band occurring at dusk and dawn. In addition, vessel noise was identified and found to exhibit strong seasonal and spatial variation. Vessel noise was greatest during August and September at the protected site and was generally lower during the winter and spring months. These findings help establish reference acoustic indices for the kelp forests off Southern California, within and outside of a protected area, and can provide resource managers with information on how well a marine reserve protects a species of interest, as well as the putative human visitation of these protected areas.

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Genetic diversity and population structure of sickleweed (Falcaria vulgaris; Apiaceae) in the upper Midwest USA - Sarbottam Piya; Madhav P. Nepal; Jack L. Butler; Gary E. Larson; Achal Neupane (Biological Invasions, 2014)

Caffeic Acid-Induced Changes in Plant–Water Relationships and Photosynthesis in Leafy Spurge Euphorbia esula - Richard R. Barkosky; Frank A. Einhellig; Jack L. Butler (Journal of Chemical Ecology, 2000)

Mechanisms of Hydroquinone-Induced Growth Reduction in Leafy Spurge - Richard R. Barkosky; Jack L. Butler; Frank A. Einhellig (Journal of Chemical Ecology, 1999)